Smart, programmable and responsive injectable hydrogels for controlled release of cargo osteoporosis drugs - Papathanasiou, Konstantinos E.; Turhanen, Petri; Brueckner, Stephan I.; Brunner, Eike; Demadis, Konstantinos D. (Scientific Reports, 2017)
Easy-to-prepare drug delivery systems, based on smart, silica gels have been synthesized, characterized, and studied as hosts in the controlled release of bisphosphonates. They exhibit variable release rates and final % release, depending on the nature of bisphosphonate (side-chain length, hydro-philicity/-phobicity, water-solubility), cations present, pH and temperature. These gels are robust, injectable, re-loadable and re-usable.
CRIS-Team Scopus Importer:2022-04-14